2020
DOI: 10.1021/jasms.9b00122
|View full text |Cite
|
Sign up to set email alerts
|

Native LESA TWIMS-MSI: Spatial, Conformational, and Mass Analysis of Proteins and Protein Complexes

Abstract: We have previously demonstrated native liquid extraction surface analysis (LESA) mass spectrometry imaging of small intact proteins in thin tissue sections. We also showed calculation of collision cross sections for specific proteins extracted from discrete locations in tissue by LESA traveling wave ion mobility spectrometry (TWIMS). Here, we demonstrate an integrated native LESA TWIMS mass spectrometry imaging (MSI) workflow, in which ion mobility separation is central to the imaging experiment and which prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 33 publications
4
49
0
Order By: Relevance
“…60,74,75 For example, TWIMS has been coupled to many ion sources including MALDI, 36,[76][77][78][79][80] DESI, 60,74,80,81 LAESI, 82,83 and LESA (Figure 2A-D). 48,61,84,85 is a point of much discussion in the scientific community. [85][86][87] In another example, Hale and colleagues showed that mobility information provided by TWIMS enabled filtering of spectral noise that contributed to improved ion image quality.…”
Section: Traveling Wave Ion Mobility Spectrometrymentioning
confidence: 99%
See 3 more Smart Citations
“…60,74,75 For example, TWIMS has been coupled to many ion sources including MALDI, 36,[76][77][78][79][80] DESI, 60,74,80,81 LAESI, 82,83 and LESA (Figure 2A-D). 48,61,84,85 is a point of much discussion in the scientific community. [85][86][87] In another example, Hale and colleagues showed that mobility information provided by TWIMS enabled filtering of spectral noise that contributed to improved ion image quality.…”
Section: Traveling Wave Ion Mobility Spectrometrymentioning
confidence: 99%
“…[85][86][87] In another example, Hale and colleagues showed that mobility information provided by TWIMS enabled filtering of spectral noise that contributed to improved ion image quality. 61 For example, the authors…”
Section: Traveling Wave Ion Mobility Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…(Right) Mass spectrum of an intact hemoglobin heterotetramer (+16) and heterodimer (+11) sampled directly from the tissue section labeled by a red square in the left panel, which marks the position of the renal pelvis, which is rich in blood vessels. Adapted with permission from ref ( 71 ). Copyright (2020) American Chemical Society.…”
Section: Ambient Surface Msmentioning
confidence: 99%